2017
DOI: 10.11604/pamj.2017.27.145.10883
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in rpoB and katG genes of multidrug resistant mycobacterium tuberculosis undetectable using genotyping diagnostic methods

Abstract: IntroductionTuberculosis remains the leading causes of death worldwide with frequencies of mutations in rifampicin and isoniazid resistant Mycobacterium tuberculosis isolates varying according to geographical location. There is limited information in Zimbabwe on specific antibiotic resistance gene mutation patterns in MTB and hence, increased rate of discordant results and mortality due to inappropriate antibiotic prescriptions. The rpoB and katG genes molecular markers are used for detecting rifampicin and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…suggested that variations may exist in different ethnic groups and geographic locations [24], most reports have shown mutations in codon 531 to be the most frequent, leading to the conclusion that codon 531 is the most prevalent region associated with rifampicin resistance [24][25][26][27][28][29][30]. Given the observation in this study, however, there may be need to carry out further investigation into the geographical variations.…”
Section: Discussionmentioning
confidence: 85%
“…suggested that variations may exist in different ethnic groups and geographic locations [24], most reports have shown mutations in codon 531 to be the most frequent, leading to the conclusion that codon 531 is the most prevalent region associated with rifampicin resistance [24][25][26][27][28][29][30]. Given the observation in this study, however, there may be need to carry out further investigation into the geographical variations.…”
Section: Discussionmentioning
confidence: 85%
“…39,40 To cater the geographic specificity of the target genes and be able to detect more possible mutations in different geographical areas, it is necessary to improve molecular assay kit diagnosis. 41,42…”
Section: Discussionmentioning
confidence: 99%
“…This evidence of association between codon variation and the resistant strains can be used further in targeted mutation screening for identification of drug resistance and non-drug resistant regions can be new targets for drug discovery process. The demonstrations of codon variation in hotspot region and also outside resistant determining region will have implications in diagnostics of TB and drug development process 23.…”
Section: Resultsmentioning
confidence: 99%